New Approaches to the Materiality of Text in the Ancient Mediterranean - Angliker, Erica; Bultrighini, Ilaria (Brepols, 2023)
In recent years, the study of epigraphy and ancient writings has undergone a ‘material turn’, as scholars have increasingly looked beyond just the contents of written sources to also focus on their broader material and visual contexts as a way of exploring the layers of different meanings that can attach to written evidence. Taking this interdisciplinary approach as its starting point, this volume draws together contributions from specialists in different fields in order to analyze text-bearing objects and monuments from across the ancient Mediterranean world. From texts inscribed on large stone monuments and buildings, clay, or metal tablets, to writings on papyrus and parchment rolls, jewellery, vases, coins, and textiles, writing on different materials had manifold possibilities. The case studies gathered here examine novel approaches to the creation and display of inscribed objects, as well as to the ways in which such items were approached and perceived by people during a chronological period ranging from the Late Bronze Age to Late Antiquity. In doing so, the volume sheds new light not only on the interplay between ancient texts, text-bearers, and viewers within their wider spatial and physical contexts, but also on the possibilities opened by exploring the material aspects of writing through interdisciplinary approaches.